Pharmacoeconomic evaluation of influenza vaccination programs in elderly in Italy - Iannazzo, Sergio; Sacchi, Viola (Farmeconomia. Health economics and therapeutic pathways, 2009)
Background: influenza infection is an important cause of morbidity and mortality in the elderly population, especially in the presence of underlying disease. Vaccination has proven effective in the reduction of influenza-like illness (ILI) cases and influenza-related hospitalizations, drug consumption, primary care consultations and death. The aim of this study is to assess the economic impact in Italy of different prophylactic strategies (vaccination with a standard vaccine, with the innovative MF59® adjuvated vaccine and no vaccination) comparing their costs and outcomes in the elderly population. Methods: a pharmacoeconomic simulation model to estimate costs and consequences of influenza with the three intervention strategies has been developed. Health economics and demographic data are taken from specific Italian sources, and vaccine effectiveness data are taken from published literature. Direct sanitary costs are considered according to current prices and tariffes. Results: it was estimated that 9,800,000 of the about 12,000,000 people with at least 65 years currently resident in Italy can be considered at high risk for influenza complications because of underlying chronic diseases. Absence of vaccination could lead to more than 2 millions of ILI cases, and 30,000 related deaths. The reduction of cases attainable with the implementation of a vaccination program would lead to an estimated 1.5 million cases with a standard vaccine, and to 1.3 million with a strategy based on the MF59® adjuvated vaccine. The standard vaccination strategy could produce a moderate total cost increase of about € 45,000,000 (+4.3%), whereas the use of the adjuvated vaccine would lead to an estimated saving of about € 80,000,000 (-7.9%), both compared to the null option. Cost savings are mainly related to hospital admissions avoided with the use of vaccines. Incremental cost-effectiveness ratio (ICER) of the standard vaccine versus no vaccination strategy is of € 85.68 for each ILI episode avoided, and of € 4,411.42 for death avoided. The strategy based on the MF59® adjuvated vaccine dominates the other two options. Conclusions: vaccination with the MF59® adjuvated vaccine (Fluad®) results more effective and cost saving when compared with the standard vaccination or the no vaccination, thus representing the strategy of choice for the elderly population. Moreover, the standard vaccine proved to be largely cost effective with respect to the null option.